Variations of sap traps for detecting pests of rice (Oryza sativa L.) Ir nutri zinc variety by hazton plant system in Sunggal, North Sumatra, Indonesia - Ameilia Zuliyanti Siregar,; Henny Herwina,; Indah Trisnawati Dwi T, (Penerbit Universiti Kebangsaan Malaysia, 2025)
Rice (Oryza sativa) is the main food commodity for Indonesians and provisioning around 35.3 million tons in North Sumatra, Indonesia. In 2022, the harvest area in North Sumatra was 385,405 ha where the productivity was 50.76 quintal/ha and the production was 2088,584 tons. Rice production is greatly influenced by cultivation practices, plant varieties, and pest and disease attacks on rice plants. This study aimed to measure the diversity and functional role of local insects in agroecosystems at various locations and habitat types Serbajadi Village and Hamparan Perak Village, Sunggal District, Deli Serdang Regency, North Sumatra, Indonesia from May to August 2023. This research used purposive random sampling with five replicates utilizing a variation of five saps, namely rubber sap (Hevea brasiliensis), jackfruit sap (Artocarpus integra), sapodilla (Manilkara zapota), papaya sap (Carica papaya), and jatropha sap (Jatropha curcas) with the Hazton planting system. A total of 8805 individual insects were successfully collected. The highest from rubber latex (H. brasiliensis) which recorded eight orders, 29 families, and 2369 individuals, while the lowest number of insects was on J. curcas plant (JS) with eight orders and 29 families, as many as 1159 individuals. The functional status of insects was identified, namely herbivores, pollinators, predators, parasitoids, and scavengers. The richness index of rubber sap (R’=7.77), jackfruit sap trap (R’=7.73), sapodilla sap trap (R’=7.47), papaya sap trap (R’=7.10), and jatropha sap was R’= 7.05. The evenness index value consists of (E=0.88 for rubber sap; E=0.55 for jackfruit sap; E= 0.98 for sapodilla sap and papaya sap, and E=0.97 for jatropha sap), and, the diversity index varies from H' =2.98, 1.88, 3.30, 3.30, and 2.27, respectively. From the data, sap trap variance will support biological control enhancing natural pest suppression and reducing insecticide.